Directions for the Development of Agricultural Entrepreneurship - Qurbonov Alisher Boboqulovich (Research Parks Publishers, 2022)
The article is based on the specifics of agriculture and the role of entrepreneurship in this sector. The opinions of scientists conducting research in the field of agricultural entrepreneurship were also researched and analyzed. The problems and prospects of agriculture in the Republic of Uzbekistan are highlighted. Suggestions and recommendations were made to address the solution of the shortage of agricultural specialists and existing business problems.